Analisis Mekanisme Area Financing Operation (AFO) Dalam Pembiayaan Nasabah Pada PT. Bank Syariah Indonesia KC Jember Sudirman - Rifqiyan Humaidillah; Vipta Riani Okta Fianti; Mila Rosa (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Basically, sound financial financing will generate large profits for the bank itself, when compared to other service activities. However, there are many risks in the financing process at banks. Both conventional banks and Islamic banks should also use the Precautionary Principle to reduce financing risks to prevent problematic or substandard financing. Apart from being caused by consumers, the negligence of the termination officer can also result in risks to financing facilities. This study aims to find out how BSI KC Jember Sudirman regulates the financing process mechanism to make it safer and more accessible to customers. In this case, BSI KC JEMBER Sudirman has a unit called Area Financing Operation (AFO) which is in charge of checking customer files that are eligible to disburse financing funds. This type of research is descriptive qualitative and a tool to search for data by means of interviews, observation and documentation. The results of this study show that the Area Financing Operation (AFO) mechanism includes administrative functions and processes, namely ensuring the completeness of customer financing documents.